Outcomes of Nulliparous Women With Spontaneous Labor Onset Admitted to Hospitals in Preactive Versus Active Labor. (11th February 2014) - Neal, Jeremy L.; Lamp, Jane M.; Buck, Jacalyn S.; Lowe, Nancy K.; Gillespie, Shannon L.; Ryan, Sharon L.
Abstract : Introduction: The timing of when a woman is admitted to the hospital for labor care following spontaneous contraction onset may be among the most important decisions that labor attendants make because it can influence care patterns and birth outcomes. The aims of this study were to estimate the percentage of low‐risk, nulliparous women at term who are admitted to labor units prior to active labor and to evaluate the effects of the timing of admission (ie, preactive vs active labor) on labor interventions and mode of birth. Methods: Data from low‐risk, nulliparous women with spontaneous labor onset at term gestation were merged from 2 prospective studies conducted at 3 large Midwestern hospitals. Baseline characteristics, labor interventions, and outcomes were compared between groups using Fisher's exact and Mann‐Whitney U tests, as appropriate. Likelihoods for oxytocin augmentation, amniotomy, and cesarean birth were assessed by logistic regression. Results: Of the sample of 216 low‐risk nulliparous women, 114 (52.8%) were admitted in preactive labor and 102 (47.2%) were admitted in active labor. Women who were admitted in preactive labor were more likely to undergo oxytocin augmentation (84.2% and 45.1%, respectively; odds ratio [OR], 6.5; 95% confidence interval [CI], 3.43–12.27) but not amniotomy (55.3% and 61.8%, respectively; OR, 0.8; 95% CI, 0.44–1.32) when compared to women admitted in active labor. The likelihood of cesarean birth was higher for women admitted before active labor onset (15.8% and 6.9%, respectively; OR, 2.6; 95% CI, 1.02–6.37). Discussion: Many low‐risk nulliparous women with regular, spontaneous uterine contractions are admitted to labor units before active labor onset, which increases their likelihood of receiving oxytocin and giving birth via cesarean. An evidence‐based, standardized approach for labor admission decision making is recommended to decrease inadvertent admissions of women in preactive labor. When active labor cannot be diagnosed with relative certainty, observation before admission to the birthing unit is warranted.